Verbal auditory agnosia in a patient with traumatic brain injury: A case report. Issue 11 (March 2018) - Kim, Jong Min; Woo, Seung Beom; Lee, Zeeihn; Heo, Sung Jae; Park, Donghwi
Abstract: Rationale: Verbal auditory agnosia is the selective inability to recognize verbal sounds. Patients with this disorder lose the ability to understand language, write from dictation, and repeat words with reserved ability to identify nonverbal sounds. However, to the best of our knowledge, there was no report about verbal auditory agnosia in adult patient with traumatic brain injury. Patient concerns: He was able to clearly distinguish between language and nonverbal sounds, and he did not have any difficulty in identifying the environmental sounds. However, he did not follow oral commands and could not repeat and dictate words. On the other hand, he had fluent and comprehensible speech, and was able to read and understand written words and sentences. Diagnosis: Verbal auditory agnosia Intervention: He received speech therapy and cognitive rehabilitation during his hospitalization, and he practiced understanding of verbal language by providing written sentences together. Outcomes: Two months after hospitalization, he regained his ability to understand some verbal words. Six months after hospitalization, his ability to understand verbal language was improved to an understandable level when speaking slowly in front of his eyes, but his comprehension of verbal sound language was still word level, not sentence level. Lessons: This case gives us the lesson that the evaluation of auditory functions as well as cognition and language functions important for accurate diagnosis and appropriate treatment, because the verbal auditory agnosia tends to be easily misdiagnosed as hearing impairment, cognitive dysfunction and sensory aphasia.